2013
DOI: 10.1098/rspa.2013.0236
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing snake locomotion in the plane

Abstract: We develop a numerical scheme to determine which planar snake motions are optimal for locomotory efficiency, across a wide range of frictional parameter space. For a large coefficient of transverse friction, we show that retrograde travelling waves are optimal. We give an asymptotic analysis showing that the optimal wave amplitude decays as the − 1 4 power of the coefficient of transverse friction. This result agrees well with the numerical optima. At the other extreme, zero coefficient of transverse friction,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
66
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(74 citation statements)
references
References 35 publications
8
66
0
Order By: Relevance
“…Examples of these three classes of optima are shown in the snapshots on the right side of figure 1. In this study, one possible local optimum was observed with isotropic friction µ b /µ f = µ t /µ f = 1, but the efficiency gradient norm was only reduced by about two orders of magnitude from the random initial kinematics [47]. Usually computations did not converge to local optima in the vicinity of isotropic friction (orange box in figure 1).…”
mentioning
confidence: 69%
See 4 more Smart Citations
“…Examples of these three classes of optima are shown in the snapshots on the right side of figure 1. In this study, one possible local optimum was observed with isotropic friction µ b /µ f = µ t /µ f = 1, but the efficiency gradient norm was only reduced by about two orders of magnitude from the random initial kinematics [47]. Usually computations did not converge to local optima in the vicinity of isotropic friction (orange box in figure 1).…”
mentioning
confidence: 69%
“…Similar models were used in [32,37,38,47,51,53,54], and the same model was found to agree well with the motions of biological snakes in [37]. three different choices of friction coefficients.…”
mentioning
confidence: 72%
See 3 more Smart Citations